History of the Growth and Development of Education in the Early Period of Independence of the Republic of Indonesia - Walikrom, Achmad Anton Risqika (Balai Publikasi Indonesia, 2023)
The journey of education in Indonesia is interesting to study from a historical perspective. The dynamics of education in the past can be material for contemplation to build education in the future. The generation living at this time should continue to remember how education fighters pioneered education in Indonesia. This study aims to examine the development of education in Indonesia at the beginning of independence. The research method used is historical qualitative. Sources of data come from documents and literature. The results of the study show that the journey of education in Indonesia at the beginning of independence was not easy. Education must be fought for with no small sacrifice. One form of the struggle for education in Indonesia at the beginning of independence was that education was fought for through various organizations so that the forerunners of education were formed as the basis for education today